Praktik Akad Mudharabah di PT. Investree Radhika Jaya: Sistem Penadaan Dana, Mekanisme Pengembalian, dan Pembagian Keuntungan - Tita, yusra (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research analyzes the practice of mudharabah contracts at PT. Investree Radhika Jaya, with a focus on the fund allocation system, fund refund mechanisms, and profit sharing issues. Through observation and risk analysis, it was found that Investree had implemented an effective settlement mechanism and carried out a comprehensive project risk analysis. Business people at Investree also pay attention to sharia principles in every aspect of their operations, transparency, accountability and justice. The results of this research provide insight into mudharabah practices in the Investree context and the importance of considering sharia aspects and social responsibility in making business decisions